Pengaruh Pemberian Ekstrak Akar Alang-Alang terhadap Hati Mencit yang Menderita Gangguan Patologi (THE INFLUENCE OF THE ROOT OF SEDGE GRASS EXTRACTION ON LIVER OF MICES THAT TO SUFFER A PATHOLOGICAL DAMAGED) - I Ketut Berata; Ida Bagus Oka Winaya (Faculty of Veterinary Medicine, Udayana University and Published in collaboration with the Indonesia Veterinarian Association, 2003)
Abstak dapat dibaca pada Full Text Abstract can be read at Full Text